Methods for Measuring Greenhouse Gas Balances and Evaluating Mitigation Options in Smallholder Agriculture - Rosenstock, Todd S.; Rufino, Mariana C.; Butterbach-Bahl, Klaus; Wollenberg, Lini; Richards, Meryl (Springer Nature, 2016)
environmental management; air quality control; air pollution; climate change; agriculture; atmospheric protection; soil science; conservation